INVESTMENT ENVIRONMENT OF KASHKADARYA REGION: ANALYSIS OF CURRENT SITUATION AND PROBLEMS - Egamberdiev, Abboskhon Sherali ogli (THE INNOVATION ECONOMY, 2026)
The analysis of the investment environment in Qashqadaryo region is crucial for economic development and population welfare. Current challenges include insufficient digital infrastructure, bureaucratic barriers, and low internet coverage in rural areas. To attract foreign direct investment, digital transformation, improved administrative services, and public-private partnerships are necessary. This article highlights the region’s economic potential and ways to enhance its investment attractiveness.